Politikberatung für Marktwirtschaft in Transformationsstaaten: Grundlagen, Visionen und Anwendungen – Policy Advice on the Social Market Economy for Transformation Economies: Principles, Vision, and Applications - Klaus Beckmann; Christian Müller; Katrin Röpke (Peter Lang International Academic Publishers, 2012)
This book runs the gamut of political economy from theoretical and philosophical principles to the application of selected methods in giving policy advice. Its authors compare the offerings of various disciplines, in particular economics and sociology, for policy advice. The demand and supply side of this activity are discussed. The leitmotif for the articles in this book is the Social Market Economy, and a further unifying theme is the application to transformation economies in South East Europe, both within the EU and beyond. – Dieser Sammelband spannt einen Bogen von den ordnungstheoretischen und sozialphilosophischen Grundlagen wissenschaftlicher Politikberatung bis zur Anwendung ausgewählter Methoden. Die Autoren setzen sich mit unterschiedlichen Theorieangeboten für Politikberatung, Anforderungen an Politikberatung und Formen von Politikberatung auseinander. Thematisch bildet die Leitidee der Sozialen Marktwirtschaft, räumlich deren Nutzung bei der Politikberatung in den Transformationsländern Südosteuropas eine Klammer. Als Beispiele solcher Länder dienen Ungarn – bereits ein EU-Mitglied – und Albanien.
Keywords: 330